Model of the Entrepreneurial Intention of University Students in the Pearl River Delta of China - Hou, Fei; Su, Yu; Lu, Minru; Qi, Mingde (Frontiers in Psychology, 2019)
Although the entrepreneurial intention of university students has been studied from different perspectives, the results are still not convergent, and the mechanism and outcomes related to how entrepreneurial intention could be affected by different factors lack integrated investigation and comparative research. Based on emotional theory, the theory of planned behavior and entrepreneurial cognitive theory as well as from the perspective of specific situations encountered by university students, this paper attempts to explore entrepreneurial intention from three perspectives, including individual, family and school; and constructs an integrated model that includes entrepreneurial passion, role models, entrepreneurial education, entrepreneurial self-efficacy and entrepreneurial intention. Based on a survey of university students in the Pearl River Delta of China, this paper attempts to explore the intrinsic mechanism of the development of entrepreneurial intention from these three perspectives. The results show that entrepreneurial passion, role models and entrepreneurial education could have different effects on entrepreneurial intention; additionally, entrepreneurial self-efficacy plays an important mediating role. The research findings contribute to the literatures regarding the factors influencing entrepreneurial intention, provide empirical evidence to formulate policies to encourage university students' entrepreneurship practices and help to enhance effectiveness of entrepreneurship education.